Stolen Future, Broken Present The Human Significance of Climate Change - A. Collings, David (Critical Climate Change, 2014)
This book argues that climate change has a devastating effect on how we think about the future. Once several positive feedback loops in Earth's dynamic systems, such as the melting of the Arctic icecap or the drying of the Amazon, cross the point of no return, the biosphere is likely to undergo severe and irreversible warming. Nearly everything we do is premised on the assumption that the world we know will endure into the future and provide a sustaining context for our activities. But today the future of a viable biosphere, and thus the purpose of our present activities, is put into question. A disappearing future leads to a broken present, a strange incoherence in the feel of everyday life. We thus face the unprecedented challenge of salvaging a basis for our lives today. That basis, this book argues, may be found in our capacity to assume an infinite responsibility for ecological disaster and, like the biblical Job, to respond with awe to the alien voice that speaks from the whirlwind. By owning disaster and accepting our small place within the inhuman forces of the biosphere, we may discover how to live with responsibility and serenity whatever may come.